Model‐based Commissioning, a New Methodological Approach for Commissioning of Nuclear Basic Facilities. Issue 4 (12th January 2022) - Gaignebet, Alan; Chapurlat, Vincent; Zacharewicz, Grégory; Plana, Robert; Richet, Victor
ABSTRACT: This article intents first to formalize commissioning that must be seen as a crucial need and an unavoidable obligation. Second, it aims to introduce a method called COGuiNF (Commissioning Guidelines of Nuclear Facilities) which would allow to prepare in relation with MBSE processes then drive relevant activities for the commissioning of Nuclear Facilities. COGuiNF must define, formalize and feed the inherent relations to be managed between engineering and commissioning. This article focuses on the five components of the COGuiNF method.